Household food storage in Ancient Israel and Judah - Frank, Tim, 1977- (Archaeopress Publishing Ltd, 2018)
This volume serves as a source on domestic food storage in Ancient Israel and Judah by outlining important ethnographic and ancient textual and pictorial sources relevant to the discussion. These allow us to understand the motivated actions in relation to food storage, and the significance of food storage in daily life.